A Software Architecture Based on the Blockchain-Database Hybrid for Electronic Health Records - Leoratto, Tiago; Dias, Diego Roberto Colombo; Brandão, Alexandre Fonseca; Iope, Rogério Luiz [UNESP]; Brega, José Remo Ferreira [UNESP]; de Paiva Guimarães, Marcelo (Springer Nature, 2023)
Blockchain applications are regarded as a disruptive technology in the health area for working in a decentralized manner, with inherited features such as immutability, privacy, scalability, and security, and with users managing their data. We present a software architecture based on blockchain and a document-oriented database to manage and store electronic health records (EHRs). This software architecture was designed and implemented to manage EHRs of patients in the process of motor function recovery and assist the research on virtual reality and neurofunctional recovery (BRAINN_VR) at the Brazilian Institute of Neuroscience and Neurotechnology (BRAINN). This solution allows BRAINN_VR researchers to analyze data while respecting the patient’s privacy. We evaluate the network performance of our solution to validate EHR insertions using four scenarios with varying data block size, network latency, and jitter. The consensus performance reached shows the feasibility of our architecture. Our software architecture has the potential to provide seamless interaction between multi-institutional research laboratories, health institutions, and patients.
Keywords: blockchain; eletronic health records; software architecture